2011
DOI: 10.1021/ac201692b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Spaces Available for Cations in Strongly Acidic Cation-Exchange Resins on the Exchange Equilibria by Quaternary Ammonium Ions and on the Hydration States of Metal Ions

Abstract: The spaces (voids) available for cations in the five exchange resins with varying exchange capacities and cross-linking degrees were estimated, on the basis of the additivity of molar volumes of the constituents. Tetraalkylammonium ions (NR(4)(+); R: Me, Et, Pr) may completely exchange potassium ion on the resin having a larger void radius. In contrast, the ratio of saturated adsorption capacity to exchange capacity of the resin having a smaller void radius decreased with an increase in size of NR(4)(+) ions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…5. 21 The nM values of monovalent ions were substantially equal to those on CG-4×8 (Fig. 2) and were independent of the resin type whether gel or porous.…”
Section: Hydration States Of Multivalent Cations and Their Coadsorptimentioning
confidence: 76%
See 3 more Smart Citations
“…5. 21 The nM values of monovalent ions were substantially equal to those on CG-4×8 (Fig. 2) and were independent of the resin type whether gel or porous.…”
Section: Hydration States Of Multivalent Cations and Their Coadsorptimentioning
confidence: 76%
“…1). 21 Quantitative exchange was observed for all QA on CG-1×2 but only for TMA + on CG-4×2 and on CG-4×8. The maximum exchange reached 98% for TEA + and 92% for TPA + on CG-4×2, and 82% for TEA + and 60% for TPA + on CG-4×8.…”
Section: Incomplete Exchange By Bulky Ammonium Ions Due To Van Der Wamentioning
confidence: 92%
See 2 more Smart Citations
“…It has been reported that the number of water molecules hydrated to some ions such as Na + and H 2 PO 4 À decreases with an increase in the ion-exchange capacity and the cross-linking degree and this experimental result can be ascribed to dehydration of the ion by a decrease in the void space for the ions in the ion-exchange resins. [22][23][24][25][26] The difference in the distribution coefficients of alkali metal ions between Naon, MCI GEL CK02A and MCI GEL CK10S may also be attributed to differences in the ion-exchange capacity and crosslinking degree of these resins (Table 1). Since Cs + has relatively large ionic size and its concentration is larger in MCI GEL CK 10S than in CK02A and Naon, the remaining void space should be smaller than in the other two resins.…”
Section: Resultsmentioning
confidence: 99%